Pengenalan Teknologi Automatic Weather Station dan Identifikasi Sumber Air dalam Mendukung Pertanian Padi Cerdas Iklim di Kabupaten Sukabumi - Satyanto Krido Saptomo; Ahmad Junaedi; Chusnul Arif; Muh Taufik; Baskoro Tri Julianto (Institut Pertanian Bogor, 2026)
Rice is a major food commodity in Indonesia, including in Pangumbahan Village, Ciracap subdistrict, Sukabumi Regency, which has great potential for rice cultivation due to its favorable climate. However, the main challenges faced are climate change and the availability of water resources. This program aims to sustainably increase rice farming productivity through the dissemination of climate-friendly agricultural technology and water resources. The program is implemented in Pangumbahan Village in collaboration between IPB team and the Ciburial Berkah Farmers Group. The methods used include field observations, mapping of potentials and problems, and the implementation of technology dissemination programs. One of the technologies introduced is the Automatic Weather Station (AWS) to monitor weather conditions in real-time, helping farmers make better decisions. The program results show that the use of AWS can enhance knowledge in agricultural irrigation planning and community welfare. The collected weather data indicates a surplus of rainwater that can be utilized for irrigation. Combined with existing water sources such as springs and wells, as well as planned irrigation from rivers, farmers will be better prepared to face the challenges of climate change and support the sustainability of rice farming in Pangumbahan Village.